Effectiveness of Short-Term Dynamic Therapy Based on Mentalization on the Reflective Capacity of Mothers and Internalizing and Externalizing Problems in Children - Darabi, Tanya; Amini, Naser; Keykhosrovani, Mouloud (Psychology of Woman Journal, 2024)
Objective: This study was conducted with the objective of examining the effectiveness of short-term dynamic therapy based on mentalization on the reflective capacity of mothers and internalizing and externalizing problems in children.Materials and Methods: The research method was a quasi-experimental design with pre-test, post-test, and control group. The population consisted of all mothers with children aged 2 to 6 years who visited counseling centers in Ahvaz in 2022. Forty participants from the population were selected using a convenience sampling method. From these, two groups of 20 were randomly selected, then one group was assigned as the intervention group and the other as the control group. The intervention protocol was based on the short-term dynamic therapy of mentalization by Mousavi and Bahrami (2020). Data were collected using the Parental Reflective Functioning Questionnaire by Luyten et al. (2017) and the Child Behavior Checklist by Achenbach and Rescorla (2001). Data analysis was performed using descriptive and inferential statistics (analysis of covariance).Findings: The results of the covariance analysis, adjusted for pre-test effects, showed that there were significant differences between the experimental and control groups in terms of reflective capacity and its components, and internalizing and externalizing problems. The therapy significantly improved reflective capacity, its components, and reduced internalizing and externalizing problems.Conclusion: Based on the results of this study, it can be concluded that short-term dynamic therapy based on mentalization can be used as an effective treatment method to improve the reflective capacity of mothers and reduce internalizing and externalizing problems in children at counseling centers.